Pembuatan Film Pendek Bersama Sanggar 16 Pekanbaru - Muhammad Kafrawi; Evizariza (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
The development of communication technology marked by the emergence of social media requires the readiness of the younger generation to provide creative content. One of the creative content that is becoming an alternative to compete nowadays is short film works. Of course, to produce a quality short film, one must have good skills in producing a work of film. Working together to produce films is one of the ways to produce quality young people in this field. It is for this reason that the dedication to making this short film is felt to be important and this community service involves members of the Pekanbaru 16 studio and several students of the Indonesian Literature Study Program FIB Unilak.